PERANAN PEMBIMBING KEMASYARAKATAN KASUS PERUNDUNGAN (BULLING) DENGAN SISTEM DIVERSI BERDASARKAN UU RI NO 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Sariadi, Banias; Herman, Asep (UNES Law Review, 2023)
In the 1945 Constitution (UUD 1945) Article 28B paragraph 2 states that children are the future of a nation that needs protection for the lives of children to guarantee the right of every child to live, grow and develop. In legal problems, children are always exposed to criminal cases which are often found in the community which always cause problems with the association of children, both as suspects and victims of a crime. Criminal cases are generally rigid and standard in nature to resolve the problem of a case with minors because it is always linked to the child's parents. Soa juvenile criminal settlement is needed which has the principle of prioritizing the best interests of the child and presenting restorative justice. Method: Using Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA) and Supreme Court Regulation (PERMA) Number 04 of 2014 concerning Guidelines for the Implementation of Diversion in the Juvenile Criminal Justice System, the process of settling child cases can be carried out outside the criminal or ordinary mechanisms known as Diversion. Findings: research results According to the SPPA Law, Differentis the transfer of settlement of child criminal cases from the criminal justice process to processes outside the criminal justice. Diversion has the goal of achieving peace between victims and children by facilitating the role of community counselors and resolving child cases outside the judicial process to prevent children from being deprived of independence and encouraging the community to participate in instilling a sense of responsibility towards children. Conclusion: Settlement of juvenile criminal cases through diversion can also be described as a system when the facilitator's role as a social advisor regulates the process of resolving conflicting parties to achieve a satisfactory resolution as restorative justice.